The handbook of global media and communication policy - Mansell, Robin; Raboy, Marc, 1948- (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2011)
"The Handbook of Global Media and Communication Policy offers insights into the boundaries of this field of study, assesses why it is important, who is affected, and with what political, economic, social and cultural consequences. Provides the most up to date and comprehensive collection of essays from top scholars in the field includes contributions from western and eastern Europe, North and Central America, Africa and Asia; offers new conceptual frameworks and new methodologies for mapping the contours of emergent global media and communication policy; draws on theory and empirical research to offer multiple perspectives on the local, national, regional and global forums in which policy debate occurs"--
Part V: Governance: new policy and research challenges. Gender and communication policy: struggling for space / Margaret Gallagher -- The environment and global media and communication policy / Richard Maxwell, Toby Miller -- Anti-terrorism and the harmonization of media and communication policy / Sandra Braman -- Regulating the Internet in the interests of children: emerging European and international approaches / Sonia Livingstone -- From television without frontiers to the digital big bang: the EU's continuous efforts to create a future-proof internal media market / Caroline Pauwels, Karen Donders -- Actors and interactions in global communication governance: the heuristic potential of a network approach / Claudia Padovani, Elena Pavan.
Includes bibliographical references and index.
Online resource; title from PDF title page (Wiley online library, viewed Oct. 13, 2011).
Keywords: Mass media policy; Mass media -- Political aspects; Communication policy; SOCIAL SCIENCE -- Media Studies; Communication policy; Mass media policy; Mass media -- Political aspects; Massamedia; Communicatie; Beleid; Internationale aspecten; Electronic books; Handboeken (vorm)